Mental States : Volume 1: Evolution, function, nature. - Schalley, Andrea C. (John Benjamins Publishing Company, 2007)
Collecting the work of linguists, psychologists, neuroscientists, archaeologists, artificial intelligence researchers and philosophers this volume presents a richly varied picture of the nature and function of mental states. Starting from questions about the cognitive capacities of the early hominin homo floresiensis, the essays proceed to the role mental representations play in guiding the behaviour of simple organisms and robots, thence to the question of which features of its environment the human brain represents and the extent to which complex cognitive skills such as language acquisition.